Atlas of transesophageal echocardiography - Nanda, Navin C; Domanski, Michael J (Williams & Wilkins, 1998)
Comprehensive, detailed atlas for residents and practitioners. Includes 1150 black and white halftones and 950 full-color illustrations. DNLM: Echocardiography, Transesophageal--atlases.
Keywords: Echocardiography, Transesophageal; echokardiografie transezofageální; radiologie, nukleární medicína a zobrazovací metody; Heart Diseases; kardiologie; nemoci srdce